ASSESSMENT OF THE CHANGES IN SOME DIAGNOSTICS ENZYMES AND OTHER PARAMETERS IN Wistar albinoRATS TREATED WITH PESTICIDES DURING GESTATION (Sciences & Technologie. C, Biotechnologies, 2005)
The present work investigates the serum enzymes activities (LDH, ALP, AST, ALT, CPK) and the level of cholesterol, glucose, triglycerides, bilirubin, creatinine, and the total protein in female rats treated with pesticides; Chlorpyrifos-ethyl and Phosalone. Pregnant rats were divided into eleven groups containing 10 individuals each, and classified intothree categories were treated orally (from the 6th to the 15th day of gestation) with different doses (1/5, 1/4, 1/3, 1/2, 2/3 LD50) of both pesticides .Animals were dissected in the 19th day of gestation, and then blood samples were collected for biochemical study. The obtained results showed that the liver is the target organ for pesticides toxicities, as indicated by the perturbations in its functions. Thus, a significant elevation in serum AST, ALT and ALP activities has been observed, while their liver activities were highly decreased. Serum cholesterol and triglycerides levels were also decreased significantly. However, after treatment with different doses of both pesticides, the liver wet weights were highly increased, whereas, the foetus weights were significantly decreased. Generally, the degrees of observed variations were found to be dose dependent.